Addition of Lateral Ganglionic Eminence to Rat Mesencephalic Grafts Affects Fiber Outgrowth but Does not Enhance Function - Mia Emgard-Mattson; Jenny Karlsson; Naoyuki Nakao; Patrik Brundin (Cell Transplantation, 1997)
Addition of embryonic striatal tissue, usually as a combination of the lateral and medial ganglionic eminences, to intrastriatal mesencephalic grafts has previously been reported to enhance recovery of drug-induced rotational behavior in the host and to modify axonal fiber outgrowth from the grafted dopaminergic neurons. This study investigated the effects of adding (cografting) either lateral or medial ganglionic eminence tissue to embryonic mesencephalic grafts implanted intrastriatally, in rats with unilateral 6-hydroxydopamine lesions. The cografts did not exhibit increased survival or cell size of dopaminergic neurons when compared to transplants of mesencephalic tissue alone. Neither did recipients of cografts exhibit any enhancement of graft-induced recovery of function, when tested for drug-induced rotational behavior or forelimb function in the staircase test. However, cografts containing lateral ganglionic eminence displayed patches of dense tyrosine hydroxylase-immunoreactive fibers within the graft tissue. These patches largely coincided with patches in adjacent stained sections, which were rich in immunostaining for the striatal-specific marker dopamine- and cyclic AMP-regulated phosphoprotein-32 (DARPP-32). Such patches were not present in rats receiving cografts containing medial ganglionic eminence or mesencephalic tissue alone. Thus, it seems that the grafted dopaminergic neurons preferentially grow into the areas of the transplants containing lateral ganglionic eminence tissue. In summary, the results suggest that embryonic lateral ganglionic eminence exerts trophic effects on the outgrowth of dopaminergic axons, but does not enhance the behavioral effects of grafted dopaminergic neurons.